EKPSPLORASI BATOK KELAPA AGAR MUDAH DI BENTUK MENGGUNAKAN LASER CUTTING - Arlyansyah, Mochamad Alief; Sadika, Fajar; Setiawan, Alvian Fajar (eProceedings of Art & Design, 2024)
Coconut shell is a by-product of coconut consumption that has several physical properties that vary depending on the age and type of coconut. Currently, the use of coconut shell as a raw material for craft products has not been accepted in the higher market because the production technique is still not well developed due to underdeveloped production techniques and lack of added value design. Development of craft making techniques using laser cutting is needed. The use of laser cutting can be an alternative in material processing because it has accuracy and efficiency in cutting coconut shells, as well as reducing material waste. In this study, the focus is on exploring the characteristics of the material so that it can be easily processed with laser cutting and identifying factors that influence the use of laser cutting technology. The research methods used include literature studies, direct observation, interviews, and exploration so that they can determine the characteristics of the material and efficiency in processing coconut shells. The results of material exploration with laser cutting technology can be used as an alternative in processing coconut shells in the form of decorative products that have high aesthetics and selling value. Keywords: coconut shells, laser cutting, crafts